The formation of subjectivity socially gifted person in the cultural-educational space as a condition of socialization - Demchenko, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
Presents the author's approach to the explanation of cultural-educational space for the development of socially gifted children, defined its parameters. Explains the importance of the development of subjectivity socially gifted person in the cultural-educational space as a condition of successful socialization and deployment capabilities. Identifies the main manifestations of subjectivity socially gifted person as the purpose and outcome of creating a space and an important indicator of its socialization. According to the analysis of the pilot study identified problems in the training of future specialists psychological-pedagogical profile to create cultural-educational space.
Keywords: socialization; giftedness; social giftedness; space; cultural-educational space for the development of social giftedness; subjectivity; subjectivity socially gifted person